2015
DOI: 10.7326/m14-1152
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Novel Regimens for the Treatment of Hepatitis C Virus

Abstract: CVS Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
220
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(231 citation statements)
references
References 44 publications
7
220
2
2
Order By: Relevance
“…More recently, additional studies have reported incremental cost-effectiveness for other genotypes. 41,42,[44][45][46] Most of the studies concluded that it is not cost-effective to treat genotypes 2-4 with the interferon-free direct-acting antiviral agents at a willingness-to-pay of $50 000 per quality-adjusted life-year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, additional studies have reported incremental cost-effectiveness for other genotypes. 41,42,[44][45][46] Most of the studies concluded that it is not cost-effective to treat genotypes 2-4 with the interferon-free direct-acting antiviral agents at a willingness-to-pay of $50 000 per quality-adjusted life-year.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] Most studies concluded that it is costeffective to treat genotype 1 with interferon-free direct-acting antiviral agents compared with pegylated interferon-ribavirin-based direct-acting antiviral agents. More recently, additional studies have reported incremental cost-effectiveness for other genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…HCV-G2 esetén a sofosbuvir-ribavirin, illetve sofosbuvir-daclatasvir 110 000 USD/QUALY, illetve 691 000 USD/QALY többletköltséggel járt a pegilált interferon plusz ribavirin kezeléshez képest, míg HCV-G3 esetén a sofosbuvir-ledipasvir-ribavirin 73 000 USD/QALY-ba, a sofosbuvir-daclatasvir pedig 396 000 USD/QALY-ba került. Amennyiben a sofosbuvir-ledipasvir ára a 6375 USD-t nem haladná meg, ez a kombináció nemcsak a leghatékonyabb és legbiztonságosabb kezelési forma lehetne HCV-G1-ben, hanem a legköltséghatékonyabb is (az AbbVie kombinációkkal nem kalkulálva) [27].…”
Section: Táblázatunclassified
“…6,7 The actual price paid by the patient may be significantly lower due to third party contracts, manufacturer rebates, and discounts. Additionally, the process of acquiring third-party prior authorization approvals for DAAs can potentially delay treatment.…”
Section: Innovations In Pharmacymentioning
confidence: 99%